Necessary lies - Chamberlain, Diane, 1950- (St. Martin's Press, 2013)
Caring for her family on their mid-20th-century tobacco farm after the loss of her parents, 15-year-old Ivy connects with Grace County social worker Jane, who strains her personal and professional relationships with her advocacy of Ivy's family, whose dark secrets test Jane's resolve against racial tensions and state-mandated sterilizations.